Challenges in Translating Idiomatic Expressions from English into Arabic - Abdalla, Nor Alhadi Hamed (Pascasarjana Universitas Negeri Makassar, 2023)
The study aims to shed light on the main challenges encounter universities students in translating idiomatic expressions from English into Arabic and to discuss some translation strategies, which can help students in translating idiomatic expressions from English into Arabic. Therefore, to meet the objectives of this study the researcher used a test consisted of (10) idiomatic expressions for collecting the data of this study. The study is based on descriptive analytical approach. The test is corrected and the results have been analyzed in figures. The main findings of the study is that students of English language really find considerable difficulties in guessing the appropriate meaning of idiomatic expressions. As well, Students’ familiarity with English language idioms is somehow low and their ability to interpret idioms is limited, also translating idioms require mastering their situational occurrences and using the suitable techniques to avoid word-to-word translation and non-equivalence. The researcher also recommends that students need to be exposed more to idiomatic expressions in schools and universities, in order to extend their knowledge.As well as to be familiar with the different idiomatic expressions, moreover, Students should always show on and practice idioms to enrich their English language vocabulary and knowledge.